A Middle Pennsylvanian macrofloral assemblage from wetland deposits in Indiana (Illinois Basin): a taxonomic contribution with biostratigraphic, paleobiogeographic, and paleoecologic implications. (12th August 2016) - Bashforth, Arden R.; DiMichele, William A.; Eble, Cortland F.; Nelson, W. John
Abstract: Taxonomic analysis is provided for a Middle Pennsylvanian macrofloral assemblage collected from clastic wetland deposits in Clay County, Indiana, on the eastern margin of the Illinois Basin. Adpressed plant fossils were recovered from four distinct beds in the lowermost Staunton Formation, positioned above the Minshall Coal (uppermost Brazil Formation), part of a succession deposited near the Atokan-Desmoinesian boundary. The assemblage of 22 fossil-taxa is dominated by pteridosperms (including Neuropteris flexuosa, Macroneuropteris scheuchzeri, Alethopteris densinervosa, Neuropteris ovata, Eusphenopteris neuropteroides, and Neuropteris missouriensis ) with lesser cordaitaleans ( Cordaites spp. indet.) and sphenopsids (particularly Sphenophyllum cuneifolium ). Lycopsids are uncommon, and ferns are rare. In contrast, the microfloral assemblage from the Minshall Coal and overlying clastic units is dominated by lycopsid and tree fern spores. Comparisons with established biozonation schemes yield different ages depending on the regional biostratigraphic framework used: (1) latest Bolsovian ( Radiizonates difformis Biozone, American microfloras); (2) latest Bolsovian or earliest Asturian ( 'Neuropteris' rarinervis Biozone, Appalachian Basin macrofloras); or (3) earliest Asturian ( Linopteris obliqua Biozone, European macrofloras). The placement and correlation of the Bolsovian-Asturian and Atokan-Desmoinesian boundaries, which have traditionally been equated by palynology, are evaluated in the context of this discordance. Several revised stratigraphic scenarios are proposed for this interval in the Illinois Basin, which is being increasingly recognized as a time of significant environmental change throughout Euramerica. Homotaxial comparisons with European macrofloral assemblages indicate that, of the 18 biological taxa recorded, between 14 and 17 (78–94%) also are common in coeval wetland deposits in Europe. The similarities exemplify the spatial conservatism and low diversity of wetland plant communities over vast areas of tropical Euramerica, a manifestation of the intrinsically stressful conditions that characterize such habitats, and indicates that neither the Laurentian Shield nor the Appalachian-Variscan Mountains were an insurmountable barrier to plant dispersal during the Middle Pennsylvanian.